Pak-Russia Geostrategic Cooperation: From Bilateralsim to Multilateral Engagement (2012-2024) - Aimen Nisar; Rabia Kosar; Nadia Awan, (ASIAN Journal of International Peace & Security (AJIPS), 2025)
This paper analyses the evolving Pak-Russia relationship within a geostrategic context, tracing the changing dynamics of their relationship from bilateral engagement to multilateral collaborations within platforms such as the Shanghai Cooperation Organization (SCO) and Pakistan’s potential engagement with BRICS. The primary focus of this paper is to address the security threats posed by various militias and non-militia groups equally to both states in the region. Employing a qualitative case study approach, the research relies on policy documents, official statements, interviews and academic literature analyzed through the lens of the complex interdependence theoretical approach. The study explores the mutual relationship regarding security, energy diplomacy and regional alignment post-2012 that has shaped this partnership. It critically examines the key events, including joint military initiatives, industrial frameworks and collaborations that underpin the cooperation. Findings reveal that while the historical mistrust and external constraints, including the Western sanctions, limited the cooperation between the states, gradually the potential for collaboration expanded in counterterrorism, energy security and regional connectivity. The research enhances the concept of multilateralism in South Asia and contributes to the collective response to emerging security threats, fostering interdependence as a pragmatic form of cooperation in a multipolar world.